The Impact of Innovative Leadership on Digital Technology Adoption in Oil and Gas Companies - Kuswanto, Hary; Kusnawan , Agus; Nugroho, Heru (Pt. Anagata Sembagi Education, 2024)
Innovative leadership is a key element in driving technological transformation in the oil and gas sector, especially in the era of digitalization and technological disruption. This study aims to explore the influence of innovative leadership dimensions, namely risk-taking ability, support for innovation, and the creation of a learning environment, on technological transformation in this sector. Quantitative method is used with a survey approach on 250 respondents who work in the oil and gas sector. The Data were analyzed using reliability, validity, and multiple linear regression tests to test the relationship between these variables. Reliability was measured by Cronbach's Alpha, while validity was tested through exploratory factor analysis (EFA). Regression models were used to assess the effect of each dimension of innovative leadership on technological transformation. The results showed that all dimensions of innovative leadership have a positive and significant influence on technological transformation, with the creation of a learning environment as the most dominant dimension. These results confirm that innovative leaders are able to create an organizational culture that is adaptive to technological change, thus accelerating the adoption of innovation in the oil and gas sector. This research provides theoretical contributions to innovative and practical leadership literature in support of policy development focused on strengthening leadership capabilities for technological transformation. With these findings, organizations in the oil and gas sector can be better prepared to face the challenges of the Industry 4.0 era through innovative leadership approaches.